Characteristics of Lusi mud volcano and its impacts on the Porong River - B D Krisnayanti; D S Agustawijaya (Brawijaya University, 2014)
Since the first gas and mud volcano spewed from well at Sidoarjo, East Java, Indonesia (called Lusi or Lapindo mud) in 2006, its keep flowing ever since. Despite the occurrence of Lusi mud volcano was debated. Either it was natural or unnatural disaster, but maintaining the impact of the mud on social and environment is important. In addition, monitoring water, land and air quality under permitable condition is urgently necessary, due to some scientist stated that the eruption of mud volcano might be impossible to stop. The Lusi’s mud was analyzed in 2009 and showed that the concentration of heavy metals were below environmental soil quality guidelines. There were no environmental effect of heavy metals (Mn, Zn, Cu, Cr, Cd, Pb, Co, Ni, Hg, and As) resulted of mud, unless when these metals are associated with other elements. In contrast, the physical and chemical of mud-water was above the environmental standard. Continues monitoring on mud and mud-water was required to protect the environment, thus human health.